2015
DOI: 10.1007/s00284-015-0853-3
|View full text |Cite
|
Sign up to set email alerts
|

Multilocus Sequence Types of Campylobacter jejuni Isolates from Different Sources in Eastern China

Abstract: Campylobacter jejuni is a major food-borne pathogen that causes human gastroenteritis in many developed countries. In our study, we applied multilocus sequence typing (MLST) technology to 167 C. jejuni isolates from diverse sources in Eastern China to examine their genetic diversity. MLST defined 94 sequence types (STs) belonging to 18 clonal complexes (CCs). Forty-five STs from 60 isolates (36%) and 22 alleles have not been previously documented in an international database. One hundred and two isolates, acco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 32 publications
(36 reference statements)
0
9
0
Order By: Relevance
“…In North China, the most frequently isolated clonal complexes were CC-21, CC-353, CC-354 and CC-443 [ 31 , 35 ], while the dominant clonal complexes of C. coli were CC-828 and CC-1150 [ 36 ]. In East China, the most common ST type of the Campylobacter strains isolated from human and food was ST-353, while the dominant ST type from chicken and food was ST-354 [ 10 ]. In Guangdong, a province in southern China, the dominant clonal complex was CC-828 [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In North China, the most frequently isolated clonal complexes were CC-21, CC-353, CC-354 and CC-443 [ 31 , 35 ], while the dominant clonal complexes of C. coli were CC-828 and CC-1150 [ 36 ]. In East China, the most common ST type of the Campylobacter strains isolated from human and food was ST-353, while the dominant ST type from chicken and food was ST-354 [ 10 ]. In Guangdong, a province in southern China, the dominant clonal complex was CC-828 [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…From 2008 to 2014, Wang et al reported that the positive rates of C. jejuni and C. coli were 18.1 and 19.0% respectively in five provinces of China [ 9 ]. Zhang et al analyzed the genetic diversity of the C. jejuni isolates in Eastern China by multilocus sequence typing (MLST) and identified 94 sequence types (STs) belonging to 18 clonal complexes (CCs) [ 10 ]. However, data on the prevalence and genetic diversity of Campylobacter is still limited in China, especially central China, which is an important transportation junction.…”
Section: Introductionmentioning
confidence: 99%
“…In the UK, CCs ST-21 and ST-45 are commonly detected in veterinary (i.e., cow, pet, sheep, and poultry) and human sources ( Manning et al, 2003 ). CCs 21, 45, 353, and 354 are also highly prevalent in sources from humans and foods in Eastern China ( Zhang et al, 2015 ). According to the results of an MLST analysis of 122 C. jejuni isolates from Danish patients with symptoms of gaostroenteritis, reactive arithritis, and Guillain–Barré syndrome, CCs ST-21, -45, and -22 are highly prevalent, accounting for 64% of all C. jejuni isolates from humans.…”
Section: Discussionmentioning
confidence: 99%
“…coli [11]. Zhang et al analyzed the genetic diversity of the C. jejuni isolates in Eastern China by multilocus sequence typing (MLST) and defined 94 sequence types (STs) belonging to 18 clonal complexes (CCs) [12]. To my best knowledge, few data were reported on the prevalence and contamination level of Campylobacter in chicken products in Central China, so the risk assessments related to food safety are also hampered by the lack of basic data.…”
Section: Introductionmentioning
confidence: 99%